2015
DOI: 10.1080/08897077.2014.960551
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Addiction and Major Mental Illness in Europe: A Narrative Review

Abstract: Integrated models implemented following US example might perform differently within the context of well-established European Union (EU) community mental health services. Such programs would require additional resources and radical redesign of service delivery systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 73 publications
2
34
0
Order By: Relevance
“…Several studies have shown, along with gender and age (e.g., Vieweg et al, 2009;Yang et al, 2011), the effects on QTc of other drugs, from multiple therapeutic classes, including antibiotics, tricyclic antidepressants, antihistamines, selective-serotonin reuptake inhibitors, and antiemetics (Beach et al, 2014;Woosley and Romero, 2015). Moreover, other factors potentially associated with QTc prolongation, such as alcohol intake (Zhang et al, 2011) and illicit substances misuse (Devlin and Henry, 2008), are highly prevalent among subjects suffering from mental disorders (Carrà et al, 2015). An extensive use of concurrent drugs due to poor physical health (e.g., Carrà et al, 2014;Clerici et al, 2014) and high rates of comorbid alcohol or substance abuse (Carrà et al, 2006) are common among people with severe mental illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown, along with gender and age (e.g., Vieweg et al, 2009;Yang et al, 2011), the effects on QTc of other drugs, from multiple therapeutic classes, including antibiotics, tricyclic antidepressants, antihistamines, selective-serotonin reuptake inhibitors, and antiemetics (Beach et al, 2014;Woosley and Romero, 2015). Moreover, other factors potentially associated with QTc prolongation, such as alcohol intake (Zhang et al, 2011) and illicit substances misuse (Devlin and Henry, 2008), are highly prevalent among subjects suffering from mental disorders (Carrà et al, 2015). An extensive use of concurrent drugs due to poor physical health (e.g., Carrà et al, 2014;Clerici et al, 2014) and high rates of comorbid alcohol or substance abuse (Carrà et al, 2006) are common among people with severe mental illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the evidence for the effectiveness of specific psychosocial interventions with this population is poor (Hunt et al, 2013). Research in the UK and internationally has concluded that the division between mental health and substance misuse services is problematic and has recommended that services become more holistic and integrated (Carrà et al 2015). Existing UK policy reflects this, with NICE guidance recommending that existing specialist services should be adapted to serve this population effectively (NICE, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that substance use disorders were strongly associated with risk of completed suicides and suicide attempts. The detrimental effect of co-occurring substance use disorders on mental disorder course was thus confirmed [2]. In particular, individuals with comorbid bipolar and substance use disorders were more likely to have a history of suicide attempt compared with their non-comorbid counterparts (23.2 versus 10.2%) [1].…”
mentioning
confidence: 62%